2023
DOI: 10.1186/s43044-023-00357-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of features and outcomes of young patients (< 45 years) presenting with ST-segment elevation myocardial infarction

Abstract: Background Coronary artery disease (CAD) is the commonest cause of death worldwide. ST-segment elevation myocardial infarction (STEMI) and its consequences can be devastating particularly at younger age for a bigger impact on the patient’s psychology and ability to work. Little is known about the differential features and outcomes of young STEMI patients in Egypt. This study characterized young STEMI patients (≤ 45 years) compared to patients > 45 years and evaluated 1-year outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…In the current study, obesity and dyslipidemia, followed by smoking, were the most prevalent risks for AMI, while HTN was the least in the young population (≤45 years) in concordance with results of Egypt Cardiorisk project Phase 1 and II, 8,9 and with Samir et al 12 The authors and Reda et al 8,9 found that smoking (which was heavy for long duration) was more in males, while obesity with associating dyslipidemia and impaired glucose metabolism were more in females. All these data were consistent with GRACE, Gulf RACE, and Gulf RACE-2, 11 but contrary to INTERHEART 2 studies, which reported a higher prevalence of HTN and DM in younger ages.…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, obesity and dyslipidemia, followed by smoking, were the most prevalent risks for AMI, while HTN was the least in the young population (≤45 years) in concordance with results of Egypt Cardiorisk project Phase 1 and II, 8,9 and with Samir et al 12 The authors and Reda et al 8,9 found that smoking (which was heavy for long duration) was more in males, while obesity with associating dyslipidemia and impaired glucose metabolism were more in females. All these data were consistent with GRACE, Gulf RACE, and Gulf RACE-2, 11 but contrary to INTERHEART 2 studies, which reported a higher prevalence of HTN and DM in younger ages.…”
Section: Discussionsupporting
confidence: 91%
“…Considering STEMI patients, expediting reperfusion is a priority to maximize myocardial salvage and minimize rates of post-MI adverse sequelae, particularly in populations with ≥ 20% of STEMI patients are in the middle age active family earners [ 34 ]. Once STEMI diagnosis is established, the contemporary evidence prioritizes prompt reperfusion by pPCI over any delays (for echocardiography, cardiac troponin or any routine laboratory workup including kidney function tests) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…The definition of 'young' in the context of AMI varies, with thresholds set at ≤40, ≤45, or ≤55 years of age [ 3 ]. While ≤45 years is generally the most accepted cutoff, the definition of premature CAD in family histories often extends to MI occurring at ≤55 years or ≤65 years for male and female relatives, respectively [ 4 ].…”
Section: Introductionmentioning
confidence: 99%